EFEK DAUN PEGAGAN (C. asiatica) SEBAGAI NEUROPROTEKTOR - Aradila Irsalina (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
The increase Of life expectancy in the global population over the past few years has resulted in the transformation of demographics, from young people to hyper-aging societies, especially in developing countries. It was reported that 12.5% (901 million) of the world's population were aged 60 years and over in 2015. The emergence of chronic and degenerative diseases are associated to high costs and it was a major concern of health and research sector in the world. The current trend is to emphasize the role of diets in aging that reflect and harmonize these global concerns. The concept of the neuroprotector has been a major area of interest for neuroscientists in recent decades because of neurological disorders involving the brain, spinal cord, and nerves that connect it more frequently. Initially, the etiology of this disorder was associated with the role of free radicals, but various pathomechanisms were explained later related to different diseases. Among these disorders, dementia is classified as a major neurocognitive disorder that interferes with cognitive function (referring to memory, speech, language, judgment, reasoning, planning and other thinking abilities) and the performance of daily activities (such as making food, paying bills and traveling to shop) which is more common among parents. Gotu kola is a traditional treatment with memory enhancers and there are several studies that underlie its neuroprotective abilities. Gotu Kola has anti-oxidative properties that are beneficial for weakening oxidative stress, strong anti-inflammatory, regenerative ability of neurons, potential prevention of neuronal damage, inhibitory effects of neurotoxicity, anti-anxiety and anti-depression properties through modulation of the GABAergic system, AChE potential in inhibition and the ability to reduce the accumulation of amyloid plaques by modulating secretory enzymes. This comprehensive multifunctional nature makes Centella asiatica a common neuroprotection agent and simultaneously targets several pathways of disease to capture neurodegenerative disorders.